Labor force participation of women in Turkey: a microeconometric analysis - Aktakke, Nazlı. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis tries to shed light on the determinants of labor force participation of married women in urban Turkey. Thesis has two main focus points; first is to find out the possible determinants of participation of women in formal work as well as different informal work states. Second focus point is to find out the effect of husband’s public health insurance coverage for women as a possible determinant of labor force participation. Binary logit models and multinomial logit models are employed as econometric tools. The results of the binary models show that effect of variables change between different income levels, especially the effect of education and number of pre-school children. In addition, results regarding the multinomial models show that the effect of determinants of labor force participation change between work states supporting the multi work state framework. While higher education levels increase formal work participation, increase in number of pre-school children drive women into informal work states as well as non-participation. Regarding husband’s health insurance coverage, in the binary models the effect is negative for general labor force participation while in the multinomial models the effect is positive for formal work and negative for informal work states. Further investigation with the inclusion of interaction terms show that the explanation for this result may be linked with the social status effect of the husband generating a negative impact for informal work while the positive impact regarding the formal work may be associated with the fact that people in similar status or occupation levels marry each other. Negative status effect of the husband for informal work states seems to be released in the case of low education of the husband or absence of wealth.
Keywords: Women -- Employment -- Turkey.; Social security -- Turkey.